Effect of hydrothermal treatment temperature on the properties of sewage sludge derived solid fuel - Mi Yan; Bayu Prabowo; Zhumin Fang; Wei Chen; Zhiqiang Jiang; Yanjun Hu (Center of Biomass & Renewable Energy (CBIORE), 2015)
High moisture content along with poor dewaterability are the main challenges for sewage sludge treatment and utilization. In this study, the effect of hydrothermal treatment at various temperature (120-200 ˚C) on the properties of sewage sludge derived solid fuel was investigated in the terms of mechanical dewatering character, drying character, calorific value and heavy metal distribution. Hydrothermal treatment (HT) followed by dewatering process significantly reduced moisture content and improved calorific value of sewage sludge with the optimum condition obtained at 140˚C. No significant alteration of drying characteristic was produced by HT. Heavy metal enrichment in solid particle was found after HT that highlighted the importance of further study regarding heavy metal behavior during combustion. However, it also implied the potential application of HT on sewage sludge for heavy metal removal from wastewater.